DETERMINATION OF PROTEIN OXIDATION IN AQUACULTURE FEED - Dragojlović, Danka (Food and Feed Research, 2021)
This research aimed to develop a reliable, easy-to-perform and cheap method for measuring protein oxidation in complex samples such as aquaculture feed within various protein sources. For that purpose modified 2,4-dinitrophenylhydrazine (DNPH)-based method for quantification of protein carbonyls was employed whilst the modification of the method consisted of using different solutions for the extraction (distilled water and different concentrations of KCl and NaCl solutions), time of protein extraction (after homogenization and over the night) and concentration of trichloracetic acid (10 and 25% TCA) for protein precipitation. Extraction during the night, higher TCA concentration and the use of 0.5 M KCl extraction solution resulted in the highest protein amount measured by the Lowry method and 280 nm protein estimation. On the other hand, the lowest protein yield was obtained by using distilled water for the extraction. Furthermore, the lowest amount of protein carbonyls was in the case when extraction was performed with distilled water (DW), while the highest content of protein carbonyls was reached with 0.15 M KCl and 0.5 M KCl extraction solutions. It was observed that the amount of protein-bound carbonyls compounds was increasing during storage under accelerated conditions and, in comparison to the original method, the modified method for measuring protein oxidation resulted in a higher amount of carbonyls during all points of storage.
Keywords: protein extraction; carbonyl content; globulin; 2,4-dinitrophenylhydrazine